2004
DOI: 10.1143/jjap.43.3934
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wet Etching Process of Pb(Zr,Ti)O3 Thin Films for Applications in Microelectromechanical System

Abstract: The wet etching of Pb(Zr,Ti)O 3 (PZT) thin films has gained considerable attention in microelectromechanical systems (MEMS) since it is economical and effective compared with dry-etching methods. In this paper, a novel wet-etching process is proposed for PZT thin film patterning using 1BHF:2HCl:4NH 4 Cl:4H 2 O solution as the etchant, where NH 4 Cl is used as an additive to decrease the undercutting of the obtained PZT pattern. According to energy dispersion spectroscopy (EDS) analysis and X-ray diffraction (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 14 publications
(17 reference statements)
1
50
1
Order By: Relevance
“…Etching of 8 μm sol-gel films by a two step HF/HCl process has been demonstrated. In this study a undercut of 2:1 lateral/thickness was observed, which is typical for dense chemical solution deposited PZT films [35,36]. However, the presence of excess porosity in a thick film increases the undercutting additionally as the etchant penetrates the film.…”
Section: Introductionmentioning
confidence: 53%
“…Etching of 8 μm sol-gel films by a two step HF/HCl process has been demonstrated. In this study a undercut of 2:1 lateral/thickness was observed, which is typical for dense chemical solution deposited PZT films [35,36]. However, the presence of excess porosity in a thick film increases the undercutting additionally as the etchant penetrates the film.…”
Section: Introductionmentioning
confidence: 53%
“…The quarter circles on front side are exposed bottom electrode pads. The 0.8 μm-thick PZT was wet etched by HCl based recipe [2]. The three white circles connected together are the top electrode of the diaphragm (centre ones) and their bonding pads.…”
Section: Thin Film Biosensorsmentioning
confidence: 99%
“…For those devices that need an accurately defined boundary of piezoelectric element, such as a cantilever, patterning or etching of the piezoelectric layer is inevitable. Feasible dry [1] and wet [2] etching processes with sufficient etching resolution have been developed for thin films. As a result, some thin film pMEMS devices have been demonstrated successfully [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to dry etching, wet etching is an effective technique in MEMS due to its high etching rate, low cost and high selectivity. In recent years, many researchers have studied Pt/PZT film fabrication using wet-etching technique [5][6][7]. However, significant undercutting was observed in the pattern.…”
Section: Introductionmentioning
confidence: 99%